Pulmonary embolism by a foreign body (polymethyl methacrylate) - G. G. Khubulava; M. A. Askerov; A. V. Krivenzov; S. V. Sadovoi; E. K. Gavrilov (Вестник хирургии имени И.И. Грекова)
A rare clinical case of material pulmonary embolism is described. After 2 month of reconstructive surgery on the spine, on the chest cavity organs X-ray picture spiral solid was revealed. Surgical intervention - removal of a foreign body of the pulmonary artery with a good result.